Workshop Desain Katalog Sebagai Trend Media Promosi Penjualan di Kabupaten Purwakarta - Dian Permata Sari; Syifaul Fuada; Lutfia Salim; Falentino Sembiring (Universitas Pendidikan Indonesia Kampus Purwakarta, 2023)
The increasing use of the internet during the Covid-19 pandemic requires people to carry out activities from home to tackle the spread of the virus. The need for innovation in shopping for sellers to meet their daily needs in serving their customers is certainly a challenge in shopping online with various obstacles and conditions. The challenge in providing information related to the goods that will be offered by buyers, of course, requires insight into presenting a product in the form of a catalog that will be loaded digitally. The product catalog is in the form of product explanations in the form of attractive images and text. Seeing the possibility of an increase in digital shopping habits, the presence or absence of Covid-19 certainly impacts the changing patterns of people's lifestyles in shopping online. Thus, the method of community service itself is carried out by preparing people in Purwakarta Regency who want to offer their products online in the form of catalog-making training, the implementation is carried out on the UPI campus in Purwakarta, and evaluation is the achievement of the training conducted by the workshop organizers. Thus, the expected results are very satisfying for the participants in terms of adding knowledge and insight, benefits and improvements in making catalog designs.